Analysis of the Elementary School Students' Learning Obstacles: A Case Study on the Concept of Fractions - Komang Sujendra Diputra; Didi Suryadi; Tatang Herman; Al Jupri (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
AbstractThe research aimed to conduct an in-depth investigation of the learning obstacles faced by elementary students in the concept of fractions. Employing a qualitative method, this study involved the fourth and fifth graders of elementary schools as the participants. The data were collected both quantitatively and qualitatively. The quantitative data were collected through a test on the concept of fractions developed by the research team. Meanwhile, the qualitative data were collected via interviews. The data were then analyzed using quantitative and qualitative methods. The results of the quantitative data analysis indicated that the average number of students who answered the overall test questions correctly was 13.33%. Through qualitative analysis, it was found that the students experienced three types of learning obstacles including epistemological, didactical, and ontogenical obstacles. Epistemological obstacles were faced by the students in the construction of fractions as parts of a whole in the visualization of the model area. Didactical obstacles occurred in the construction of fractions as parts of a whole in the visualization of discrete models and improper fractions. Ontogenical obstacles occurred in the construct of fractions as measures, especially placing fractions on the number line. The findings of this study can be used as a basis for educators to develop learning designs on the concept of fractions in elementary schools.Keywords: concept of fractions, learning obstacles, elementary school students.Â AbstrakPenelitian ini bertujuan untuk melakukan investigasi mendalam tentang hambatan belajar yang dialami siswa sekolah dasar pada konsep pecahan. Dengan menggunakan metode kualitatif, penelitian ini melibatkan siswa kelas IV dan V sekolah dasar sebagai partisipan penelitian. Data dikumpulkan secara kuantitatif maupun kualitatif. Data kuantitatif dikumpulkan melalui tes konsep pecahan yang disusun dan dikembangkan tim peneliti. Sementara itu, data kualitatif diperoleh melalui wawancara. Data yang telah diperoleh kemudian dianalisis menggunakan metode kuantitatif dan kualitatif. Hasil analisis data kuantitatif menunjukkan bahwa banyaknya siswa yang berhasil menjawab keseluruhan pertanyaan tes dengan benar adalah 13.33%. Melalui analisis kualitatif, ditemukan bahwa siswa mengalami tiga jenis hambatan belajar yaitu hambatan epistimologis, didaktis, dan ontogenis. Hambatan epistimologis dialami siswa pada konstruk pecahan sebagai bagian dari keseluruhan dalam visualisai model area. Hambatan didaktis terjadi pada konstruk pecahan sebagai bagian dari keseluruhan dalam visualisasi model diskrit serta pecahan campuran. Hambatan ontogenis terjadi pada konstruk pecahan sebagai ukuran khususnya menempatkan pecahan pada garis bilangan. Temuan pada penelitian dapat digunakan sebagai dasar bagi pendidik dalam mengembangkan desain pembelajaran pada konsep pecahan di sekolah dasar.Kata kunci: konsep pecahan, hambatan belajar, siswa sekolah dasar.